QUANTITATIVE DETERMINATION AND PREPARATIVE ISOLATION OF TWO MAJOR ALKALOIDS FROM THE VIETNAMESE MEDICINAL HERB EVODIAE FRUCTUS - NGUYEN, N. VAN T.; NGUYEN, X. DAO T.; NGUYEN, K. NGAN H.; NGUYEN, T. KIEN; NGUYEN, M. PHUONG; KIM, KYEONG-HO (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: To develop a simple and accurate HPLC-DAD method for simultaneous determination, the content of major components: limonin, evodiamine, and rutaecarpine in Evodiae fructus and evaluation the quality of Evodiae fructus sold in markets. Methods: Open column chromatography was used to separate and purify rutaecarpine and evodiamine, the two major alkaloids from Evodiae fructus extract as a laboratory standard. Chromatographic separation was achieved using a Germini C18 column (150 mm × 4.6 mm I.D., 5 µm), detected at 210 nm. The mobile phase consisted of acetonitrile (A), methanol (B), and water (C). The validated method simultaneously determined alkaloid content in 40 batches of samples collected from markets in different regions of Vietnam. Results: In one-step purification, our method yielded 326 mg of rutaecarpine and 128 mg of evodiamine from 3.2 g of crude extract, with purities of 98.9 and 98.5%, respectively. The structures of these compounds were identified using 1H NMR and 13C NMR. There was a significant correlation between alkaloid content and fruit size, with a Spearman correlation coefficient of>0.5 (p<0.001), and there was a large difference in alkaloid contents between three maturity degrees of the fruit. Open-mouth fruits and fruits with average sizes of 4 to 6 mm had the highest alkaloid contents, whereas closed-mouth fruits had the lowest. Conclusion: This study provided information on the standardization and quality control of evodiamine and rutaecarpine in Evodiae fructus, as well as a foundation for further pharmacological and toxicological studies.